Ecological and hygienic estimation of the construction materials filled with crushed polymer waste with surfactants deposited on the surface in aggressive environments (Environment & Health, 2019)
The purpose: ecological and hygienic assessment of building materials made of cement-sand compositions filled with crushed polymer waste with surfactants deposited on the surface in aggressive environments.Materials and methods of research. Hygienic properties of materials made of cement-sand compositions filled with recycled polymer waste with surfactants applied on their surface in aggressive aqueous media were analyzed in the course of laboratory instrumental research in the certified laboratory centers of the Ivano-Frankivsk National Medical University and Ivano-Frankivsk Regional Laboratory Center of the Ministry of Health of Ukraine during the conducting of the research No.0117U004237. It allowed to determine the impact of various aggressive environments on chemical destruction of materials to conduct sanitary and hygienic assessment of the impact of degradation products on the environment.The research was conducted using household and industrial waste: polyethylene terephthalate (PETF), polyvinyl chloride (PVC) and polyethylene and polypropylene mixtures (PE + PP); slag-portland cement (MPS) M-400 produced by PJSC "Ivano-Frankivsk Cement"; river sand fraction 0,5-1,0 mm; shredder machine; a sword-cutter for paper; device for mechanical activation of polymer waste; a device for spray-type surfactant application; mixer; laboratory weighing scales; photoelektrokolorymeter CPK-2; pH meter of the laboratory with an error of measurement ± 0,1 units pH; 0.01% NaCl solution; sodium laureth sulphate, sulfuric acid (density 1.83 g / cm3 ) methylene blue, phenolphthalein and necessary equipment for titration.Results and discussion. The results of hygienic research revealed that the lowest amount of degradation products is released from samples filled with: PETF, from 2% to 10% of the total weight of the filler, when there is a sharp decrease in the mass loss of samples due to the washing out of CaO under conditions of carbon dioxide and extensive corrosion, as well as in the rain and distilled waters. Acceleration of destruction is specific for the magnesian environment; PVC from 2% to 11% there is a sharp decrease in the mass loss of samples in conditions of all model corrosion environments, as well as in rain and distilled waters; a mixture of PE + PP, from 0.25% to 2.25% under conditions of all model aggressive environments and in rain and distilled waters. Exceeding of MACs for drinking water was not detected in samples tested.Conclusions and perspectives. Hygienic studies have found that the product of destruction of samples of cement-sand compositions filled with polymers is a mixture of inorganic amorphous sediment, the main mass of which are: CaO, Ca(OH)2, Ca(HNO3)2, from 97.83% to 98.46% of the total mass of sediment, other - Mg(OH)2, Al2(OH)3. Destruction products are non-toxic insoluble or slightly soluble simple inorganic compounds that have no negative impact on the environment and humans.
Keywords: hygienic assessment; municipal hygiene; surfactants; polymer processing; cement-sand mixture